Kedudukan Keterangan Saksi Dalam Pembuatan Putusan Pidana Berkaitan Dengan Pasal 169 KUHAP (Studi Putusan Nomor: 575/Pid.B/2020/PN Cbi) - Wanda Eka Sri Masrita; Fanny Tanuwijaya; Samuel Saut Martua Samosir (Mimbar Yustitia: Jurnal Hukum dan Hak Asasi Manusia)
A court decision is a judge's statement regarding the criminal justice process issued by the court. The verdict contains all the facts and circumstances related to the evidence and the judge's considerations at the trial. One of the pieces of evidence is witness testimony. The position of witness testimony occupies the first position in the hierarchy of Article 184 of the Criminal Procedure Code. Then how can a witness who is still in a husband and wife relationship with the defendant be used as evidence? However, the verdict is not explained explicitly in accordance with the provisions of Article 169 of the Criminal Procedure Code. If the verdict is not explained in detail, it will cause ambiguity. The author uses a normative legal research method with a statutory and conceptual approach. The verdict does not explicitly state that the witness has received approval from the public prosecutor and the defendant and the witness want it. Based on the provisions of Article 168 letter c of the Criminal Procedure Code, the testimony of a wife or husband who has a relationship with the defendant cannot be heard and can be withdrawn. A good verdict, the judge in his considerations must explain the facts and circumstances accompanied by evidence that proves the defendant's guilt. The results of this study are that a good verdict must contain all the facts during the trial process to ensure justice, certainty and benefit to the community.